2011
DOI: 10.1158/0008-5472.can-10-2887
|View full text |Cite|
|
Sign up to set email alerts
|

Oncogenic Synergism between ErbB1, Nucleolin, and Mutant Ras

Abstract: Alterations in the ErbB family of growth factor receptors, their signaling components, and mutational activation of Ras proteins are major contributors to malignant transformation. Recently, mutant Ras was shown to be capable of activating ErbB receptors in a ligand-independent manner. Furthermore, it was observed that nucleolin, a transcriptional regulator and ribosome biogenesis factor, can bind both K-Ras and the cytoplasmic tail of ErbB receptors to enhance ErbB receptor activation. However, the functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 46 publications
3
72
0
Order By: Relevance
“…This is compatible with the fact that the gene network controlling the maintenance of aggressive phenotype appears mainly under positive control by miRNAs (Polyak and Weinberg, 2009;Inui et al, 2010;Martello et al, 2010), whereas the effects on proliferation might not reveal immediate phenotypic consequences in virtue of the "balancing effect" between miRNAs favoring and opposing the same process (Ventura and Jacks, 2009). Moreover, our data are in agreement with previously published data demonstrating that NCL also exerts an miRNA-independent role in cancer cell proliferation and tumorigenicity (Shi et al, 2007;Reyes-Reyes and Akiyama, 2008;El Khoury et al, 2010;Destouches et al, 2011;Farin et al, 2011;Wu et al, 2012). This is the first study of the functional role of NCL in miRNA regulation with clear clinical implications.…”
Section: Figure 9 Ncl-targeting Compound Interferes With Aggressivensupporting
confidence: 94%
See 1 more Smart Citation
“…This is compatible with the fact that the gene network controlling the maintenance of aggressive phenotype appears mainly under positive control by miRNAs (Polyak and Weinberg, 2009;Inui et al, 2010;Martello et al, 2010), whereas the effects on proliferation might not reveal immediate phenotypic consequences in virtue of the "balancing effect" between miRNAs favoring and opposing the same process (Ventura and Jacks, 2009). Moreover, our data are in agreement with previously published data demonstrating that NCL also exerts an miRNA-independent role in cancer cell proliferation and tumorigenicity (Shi et al, 2007;Reyes-Reyes and Akiyama, 2008;El Khoury et al, 2010;Destouches et al, 2011;Farin et al, 2011;Wu et al, 2012). This is the first study of the functional role of NCL in miRNA regulation with clear clinical implications.…”
Section: Figure 9 Ncl-targeting Compound Interferes With Aggressivensupporting
confidence: 94%
“…These findings support the idea that NCL might be considered a cancer cell-specific receptor that is able to mediate tumor-selective uptake of specific molecules. The importance of NCL in cancer biology was recently highlighted by studies showing that NCL plays a critical role in tumorigenesis and angiogenesis (Shi et al, 2007;Reyes-Reyes and Akiyama, 2008;El Khoury et al, 2010;Destouches et al, 2011;Farin et al, 2011;Wu et al, 2012). Furthermore, the ability of this protein to bind specific RNA and G-rich DNA elements with high affinity (Brooks and Hurley, 2010;Abdelmohsen et al, 2011;Sun et al, 2011) makes it targetable by the first G-rich aptamer (AS1411) that has reached phase II clinical trials for cancer therapy (Teng et al, 2007;Soundararajan et al, 2008;Bates et al, 2009a;Keefe et al, 2010).…”
mentioning
confidence: 99%
“…In our earlier studies, we have identified a functional crosstalk between Ras, nucleolin and ErbB1 [22, 24]. In the present study we examined the effect of two drugs, directed towards Ras and nucleolin proteins, as a tool to disrupt the synergism between these three oncogenes as a potential treatment for glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction leads to ErbB1/EGFR receptor activation as well as to colony growth in soft agar [20]. In addition, recently we identified a crosstalk between nucleolin, ErbB1 and Ras proteins [22]. More recently, we have demonstrated that treatment of colon and prostate cancer cells with FTS and GroA (AS1411) inhibited cell growth and anchorage independent growth [24].…”
Section: Introductionmentioning
confidence: 99%
“…4A and B). Furthermore, accumulating evidence has shown that cytoplasmic NCL interacts with erbB receptors, and especially enhances epidermal growth factor receptors (EGFRs), thereby enhancing EGFR dimerization and activation and promoting EGF ligand-independent cell growth (25,26). Therefore, we focused on EGFR as a partner of the DDX31-NCL complex and performed immunoprecipitation with an anti-EGFR antibody, followed by Western blot with NCL and DDX31 antibodies.…”
Section: A Tri-complex Of Ddx31 Nucleolin and Egfr Regulates Egfr-akmentioning
confidence: 99%